Avaliation of the effects of using Aloe vera gel in the early growth of seedlings of economic interest - Davalo, Marcio Jara; Rondon, Josimara Nolasco; Rezende, Rosalina Aparecida Ferreira de; Peruca, Ricardo Dias; Souza, Antonio Pancracio de; Carvalho, Cristiano Marcelo Espinola; Fabri, João Roberto; Itavo, Luiz Carlos Vinhas (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aimed to test the use of fresh gel of Aloe barbadensis Miller plant in cultivation, substituting commercial agar as an alternative means of lowering costs, and provide an innovative approach in its use. Plants growing in a substrate of Aloe and consistently showed lower growth rate than plants grown in soil. Results indicated that Aloe benefits promoted in the initial growth, but with increasing cultivation time, parts of the plant ceased growing. However, the period of emergence of new leaves is similar to that of plants grown in soil. The determination of the dry mass also did not differ between treatments, showing that carbon assimilation was not affected by the substrate of aloe. Finally, it is clear that aloe vera might become a key element in experiments on growing plants under controlled conditions for being an excellent nutrient and moisturizer.